Muatan sedimen terampai dan perkaitannya dengan penghasilan muatan sedimen pada musimkering dan hujan di Tasik Chini, Pahang - Nurul Syazwani Ab Rani,; Mohd Ekhwan Hj Toriman,; Mushrifah Hj Idris,; Nor Rohaizah Jamil,; Mohd Khairul Amri Kamarudin, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Suspended sediment yield from Sg Chini, which is one of the active feeder river in Chini Lake, Pahang was studied for two different seasons, namely the normal and rainy seasons at three selected stations. In this study, the data was observed on 16/08/08, 31/08/08 and 13/09/08 which representing normal season, while 4/12/08, 25/12/08 and 25/01/09 are rainy season. Two parameters were measured at each station, namely the river discharge (Q) (m3/s) and sediment concentration (mg/L). The result shows that, the estimation of Q values for normal day ranged between 48,608,640 L/day, 86,875,200 L/day and 95,264,640 L/day. Meanwhile during rainfall season, the Q estimation ranged between 66,795,840 L/day, 381,801,600 L/day and 300,888,000 L/day. Average of suspended sediments concentration (SSC) based on three sampling stations show different values for the two different seasons. The sampling on 16/08/08 indicates that average SSC is 17.2 mg/L, 42 mg/L and 22.4 mg/L, on 31/08/08 was recorded 32.8 mg/L, 37.6 mg/L and 36.8 mg/L, 17.6 mg/L, 38.4 mg/L and 38.8 mg/L was recorded o 13/09/08. Meanwhile, the SSC during rainfall is 28.8 mg/L, 56 mg/L and 71.2 mg/L was recorded on 4/12/08, while the sampling on 25/12/08 indicates that the average SSC is 21.6 mg/L, 19.6 mg/L and 39.2 mg/L, and also 20.8 mg/L, 42.8 mg/L and 36 mg/L on 25/01/09. When converted to the average suspended sediment yield in term of square km, the estimation value for suspended sediment yield that transported from Chini river is 20,984.52 kg/km2/year (20.65 tonnes/km2/year) during normal day and 86,248.68 kg/km2/year (84.88 tonnes/km2/year) during rainfall